Strategi Pembangunan Sektor Kelautan dan Perikanan Berbasis Wilayah pada Satuan Wilayah Pengembangan (SWP) Bagian Selatan Provinsi Sulawesi Selatan - Nurul Wahdaniyah; Jufriadi Jufriadi; Fadhil Surur (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2018)
Regional-based development of the marine and fisheries sector has undergone a change in its way of thinking from mainland-oriented to marine-oriented with the concept of sustainable development. In the Regional Spatial Plan (RTRW) of South Sulawesi Province 2009 until 2029, the southern Regional Development Unit (SWP) covers Jeneponto regency, Bantaeng regency, Bulukumba regency and Selayar Islands regency, which have very potential marine and fisheries sector. This research aims to determine the potential of the marine and fisheries sector in the southern SWP of South Sulawesi Province, to determine the hierarchy of development centers of marine and fisheries sector in the region, and to understand the regional-based development strategies of marine and fisheries sector. The methods used are quantitative analysis utilizing Location Quotient (LQ), Shift-Share, Scalogram, and Strength Weakness Opportunity Threat (SWOT) methods. Results of the analysis shows that leading sector in Jeneponto regency is fishponds, in Bantaeng regency is sea cultivation, in Bulukumba Regency are sea cultivation, fishponds and ricefields, mean while in Selayar Islands regency is capture fishery. As for development centers of the marine and fisheries sector, in Bulukumba regency is classified as hierarchy 1, Bantaeng regency as hierarchy 2, Selayar Island regency as hierarchy 3, and Jeneponto regency as hierarchy 4. Development strategy of marine and fisheries sector at the southern SWP South Sulawesi Province is based on the region and local economy.